The Effects of Carbon Emission Intensity, Green Process Innovation and Top Management Team Characteristics on Firm Performance - Vera Nabila; Juniati Gunawan (Journal of Accounting and Finance Management, 2026)
Climate change and environmental degradation driven by excessive fossil fuel consumption in the energy sector have intensified concerns regarding carbon emissions and their implications on firm performance. In response to these challenges, firms are increasingly required to manage environmental impacts, adopt green process innovation, and strengthen managerial effectiveness. This study aims to analyze the effects of carbon emission intensity, green process innovation, and top management team characteristics on firm performance by examining companies in the Indonesian energy sector during the 2022–2024 period. A total of 101 observations were selected using a purposive sampling method. Using regression analysis, the results show that carbon emission intensity has a negative effect on firm performance, green process innovation does not have a significant effect, and top management team characteristics simultaneously influence firm performance, with the age of the Chief Executive Officer having a negative partial effect. These findings indicate that environmental performance and managerial characteristics play an important role in shaping firm performance in the energy sector.